Muslim couples: The role of dyadic coping in buffering the effects of perceived religion-based couple discrimination on relationship satisfaction - Genc, Emel (Kansas State University, 2019)
Muslims are one of the most discriminated groups and frequent targets of negative stereotype and discrimination, especially after the attacks on the U.S. by Muslim terrorists on September 11, 2011. Although there is sufficient evidence of discrimination toward Muslim adults in the U.S., there is limited information specific to Muslim couples. Studies on minority couples claim that the social disapproval and discrimination experience result in adverse relationship outcomes, however how couples cope with discrimination is unclear. This study examined the relationship between religious congruity and clothing style with religion-based couple discrimination and how dyadic coping moderates the mediating effects of couple negative interaction on the relationship between partners and relationship satisfaction. Participants were 129 Muslim couples residing in the U.S. Results indicated that men’s clothing style and feeling religiously congruent with the community were related to the perception of discrimination. Further, perceiving discrimination was linked with destructive interaction between couples, which caused lower relationship satisfaction. However, couples’ abilities to cope with stress reduced the indirect effect of perceived religion-based couple discrimination on relationship satisfaction.
Keywords: Discrimination; Dyadic coping; Muslim; Negative interaction; Religious congruity; Relationship satisfaction